RISK MANAGEMENT AND PILGRIM SAFETY: A COMPREHENSIVE STRATEGY FOR ORGANISING HAJJ AND UMRAH - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2024)
The organisation of Hajj and Umrah presents unique challenges in risk management and pilgrim safety, given the large scale and complexity of these events. The study in this research uses the literature research method. The results show that the integration of advanced technologies, such as geographic information systems and artificial intelligence, with traditional risk management procedures is highly effective in identifying, assessing, and mitigating risks. The research also emphasises the importance of cross-sectoral collaboration, intensive training and continuous education in building a strong safety culture. Furthermore, the study underscores the crucial role of a coordinated and adaptive emergency response system, as well as the importance of post-event evaluation for continuous improvement.